Prevalence of intestinal parasites in referred individuals to the medical centers of Tonekabon city, Mazandaran province - Shahdoust, Samira (Gastroenterol Hepatol Bed Bench, 2016)
AIM: The aim of the present study was to determine the prevalence of intestinal parasites and their relation with socio-demographic data in referred individuals to the medical centers in Tonekabon, Mazandaran province, 2015. BACKGROUND: Due to the climatic and ecological conditions in Mazandaran province, determination of the status of intestinal parasites among referred individuals to the medical centers of Tonekabon city can help researchers and healthcare services to prevent and/or control of parasitic infection in this region. METHODS: This cross sectional study was conducted with randomized sampling in 2015 on 820 stool samples. Stool samples were assessed using direct slide smear with saline and Lugol, formalin-ether concentration, Ziehl-Neelsen and trichrome staining. Polymerase Chain Reaction (PCR) using specific primers was conducted for the samples suspected for Entamoeba histolytica/E. dispar and Cryptosporidium spp. One Cryptosporidium positive sample in this study was submitted for sequencing. RESULTS: A total of 444 (54.1%) and 376 (45.9%) were male and female, respectively. Furthermore, 495 (60.4%) and 325 (39.6%) of participants had lived in the urban and rural areas, respectively. Overall, 222 participants (27.1%) were infected with at least one intestinal parasites. Prevalence of pathogenic protozoa (Giardia lamblia and Cryptosporidium spp.) and helminthes parasites was calculated as 3.1 and 1.2%, respectively. The most common intestinal parasites in this area were: Blastocystis 153 (18.7%), Endolymax nana 44 (5.4%), Entamoeba coli 40 (4.9%), Giardia lamblia 25 (3%), Iodamoeba butschlii 22 (2.7%), Ascaris 5 (0.6%), Enterobius vermicularis 4 (0.5%), Trichostrongylus 1 (0.1%) and Cryptosporidium 1 (0.1%). By sequencing of the positive Cryptosporidium isolate using Gp60 gene, Cryptosporidium parvum subtype ΠaA16G2R1 was diagnosed. CONCLUSION: Protozoa were more abundant than helminthes and Giardia lamblia was the most common protozoan pathogen. In this study, no significant association was found between the prevalence and the variables of socio-demographic data. Adequate knowledge and periodic surveillance of the prevalence of parasites and the socio-demographic variables that affect their frequency is important for effective control of parasitic infections.